Genome-wide association analysis of milk production, somatic cell score, and body conformation traits in Holstein cows - Wang, Peng; Li, Xue; Zhu, Yihao; Wei, Jiani; Zhang, Chaoxin; Kong, Qingfang; Nie, Xu; Zhang, Qi; Wang, Zhipeng (Frontiers in Veterinary Science, 2022)
Milk production and body conformation traits are critical economic traits for dairy cows. To understand the basic genetic structure for those traits, a GWAS was performed on milk yield, milk fat yield, milk fat percentage, milk protein yield, milk protein percentage, somatic cell score, body form composite index, daily capacity composite index, feed, and leg conformation traits, based on the Illumina Bovine HD100k BeadChip. A total of 57, 12 and 26 SNPs were found to be related to the milk production, somatic cell score and body conformation traits in the Holstein cattle. Seven significant SNPs were associated with multi-traits and were located on the PLEC, PLEKHA5, TONSL, PTGER4, and LCORL genes. In addition, some important candidate genes, like GPAT3, CEBPB, AGO2, SLC37A1, and FNDC3B, were found to participate in fat metabolism or mammary gland development. The results were validated in a different Holstein population and are useful for further genetic analysis that would improve milk production and quality.